Konstruksi Epistemologis Fikih Feminis: Epistemological Construction Of Feminist Fiqh - M. Ishaq (An-Nisa’ Journal of Gender Studies, 2010)
This article discusses Feminist Fiqh Construction, as a form of renewal in the interpretation of Islamic fiqh that focuses more on gender relations issues. In addition to being more empowerment-oriented, the epistemological construction of feminist fiqh also has its own characteristics that differ from the construction of fiqh in general. Therefore, Feminist Fiqh offers new hope for the creation of more humane gender relations. This discussion emphasizes the process of forming the Feminist Fiqh construction with an applied research orientation (tahbiqu al-ijtihad). Tulisan ini membahas seputar Konstruksi Fikih Feminis, sebagai salah satu bentuk pembaharuan penafsiran fikih Islam yang lebih fokus pada persoalan relasi-relasi gender. Kecuali lebih berorientasi pada pemberdayaan, konstruksi epistemologis fikih feminis juga mempunyai karakteristik tersendiri yang berbeda dengan konstruksi fikih pada umumnya. Oleh karenanya, Fikih feminis memberikan harapan baru bagi terciptanya relasi gender yang lebih manusiawi. Uraian ini lebih ditekankan pada proses pembentukan konstruksi fikih feminis dengan orientasi applied research (tahbiqu al-ijtihad).